MEMBANGUN PROTECTION ASSISTANCE WEBSITE (PAW) UNTUK MENDETEKSI KECURANGAN PADA SITUS E-COMMERCE - Mustafa Ramadhan; Maya Amelia; Terttiaavini Terttiaavini (UNIVERSITAS INDO GLOBAL MANDIRI)
The current Internet usage is increasing. This becomes an attraction for investors to develop a virtual world business. The term e-commerce is a web application sites that provide business services. Increased transaction penjulan virtual world inviting people to commit a crime. The difficulty of detecting sites that indicated fraud and lax government regulations become obstacles in memberatas crime in cyberspace. One type of crime that often occurs is a fraud transaction. Variety crimes committed in fraud transaction is the purchase of goods that are not in accordance with the order (specification drawings), goods that were never sent, or the goods are delivered in damaged condition etc. To overcome these necessary precautions. One of them is building a website application assistance Protection (PAW) which can provide information about the legality of an e-commerce site. Basic web quality assessment using the method and problem-solving techniques using decesion tree method. While tTahap software development using Web Development Life Cycle. PAW is an application that contains questions that lead to the testing of e-commerce sites. PAW can be an effective detection applications. PAW is built with the concept of smart application, user friendly and easy to use, so it can be used by many users.Key word : E-commerce, Webequaly, Web Development Life Cycle, Decision Tree